Machine gun preacher [videorecording (DVD)] - Forster, Marc, 1969-; Butler, Gerard, 1969-; Monaghan, Michelle; Baker, Kathy, 1950- (2012)
Sam Childers is a drug-dealing criminal who undergoes an astonishing spiritual transformation and makes a life-changing decision to travel to war-torn East Africa. After witnessing unspeakable horrors faced by innocent children, he vows to save them at any cost, including his own safety. Childers begins waging a relentless battle against the territory's renegade militia, leading harrowing missions behind enemy lines to rescue kidnapped orphans and restore peace to their lives and eventually his own.